Pengaruh Motivasi Kerja, Komitmen Kerja, dan Kepuasan Kerja terhadap Kinerja Karyawan pada PT Bolon Jaya Karya - Rumahorbo, Kevin Andreas; Otakfianus Telaumbanua; Angga Saputra (Journal of Management and Bussines (JOMB), 2026)
This study aims to analyze the influence of work motivation, work commitment, and job satisfaction on employee performance at PT Bolon Jaya Karya. The research method used was quantitative with an explanatory research approach. The population in this study consisted of 128 employees, and the entire population was sampled using a saturated sampling technique. Data were analyzed using multiple linear regression with the help of SPSS. The results showed that work motivation has a positive and significant effect on employee performance with a significance value of 0.047 < 0.05 and a calculated t of 2.002 > ttable 1.979. Work commitment has a positive and significant effect on employee performance with a significance value of 0.030 < 0.05 and a calculated t of 2.193 > ttable 1.979. Job satisfaction has a positive and significant effect on employee performance with a significance value of 0.045 < 0.05 and a calculated t of 2.030 > ttable 1.979. Simultaneously, work motivation, work commitment, and job satisfaction have a positive and significant effect on employee performance, with an F-value of 6.182 > F-table of 3.07 and a significance value of 0.001 < 0.05. The coefficient of determination (Adjusted R-Square) of 0.109 indicates that employee performance can be explained by work motivation, work commitment, and job satisfaction by 10.9%, while the remainder is influenced by other factors outside the study. The conclusion of this study is that work motivation, work commitment, and job satisfaction, both partially and simultaneously, have a positive and significant effect on employee performance at PT Bolon Jaya Karya.   Keywords: Work Motivation, Work Commitment, Job Satisfaction, Employee Performance, Human Resource Management